2022
DOI: 10.1371/journal.pmed.1004074
|View full text |Cite|
|
Sign up to set email alerts
|

Factors influencing appropriate use of interventions for management of women experiencing preterm birth: A mixed-methods systematic review and narrative synthesis

Abstract: Background Preterm birth-related complications are the leading cause of death in newborns and children under 5. Health outcomes of preterm newborns can be improved with appropriate use of antenatal corticosteroids (ACSs) to promote fetal lung maturity, tocolytics to delay birth, magnesium sulphate for fetal neuroprotection, and antibiotics for preterm prelabour rupture of membranes. However, there are wide disparities in the rate and consistency in the use of these interventions across settings, which may unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…For example, studies on factors affecting multiple micronutrient supplementation, iron folic acid and lipid-based nutrients reported women’s knowledge, acceptance, motivation, and attitudes towards the medication play an important role 43 44. Furthermore, a study on factors affecting use of intervention for preterm management also reported women felt hesitant to consume the medications to improve labour outcome due to fears about baby’s growth and development 45. This highlights the need to ensure that women are aware on the benefits of the supplement and given assurance on the safety of its use.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies on factors affecting multiple micronutrient supplementation, iron folic acid and lipid-based nutrients reported women’s knowledge, acceptance, motivation, and attitudes towards the medication play an important role 43 44. Furthermore, a study on factors affecting use of intervention for preterm management also reported women felt hesitant to consume the medications to improve labour outcome due to fears about baby’s growth and development 45. This highlights the need to ensure that women are aware on the benefits of the supplement and given assurance on the safety of its use.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns were also raised regarding potential tocolytic effects, and staff can be reassured that these are not founded in evidence. 20,21 Specific evidence relating to training and education in LMIC settings is lacking. However, a successful national program based in the UK (PReCePT) that aimed to increase the uptake of magnesium sulfate before preterm delivery relied heavily on the training of small numbers of staff across multiple sites who, in turn, could train other staff in interdisciplinary training, as well as infographics and patient information.…”
Section: Considerations In Lmicsmentioning
confidence: 99%
“…A systematic review investigating reasons for non‐compliance by healthcare staff to magnesium sulfate guidelines globally identified particular concerns regarding the toxicity of magnesium sulfate 20 : magnesium toxicity at the regimen suggested is very unlikely, 21 and (perhaps unlike in pre‐eclampsia) women are most likely to have preserved renal function, further reducing the risk. Concerns were also raised regarding potential tocolytic effects, and staff can be reassured that these are not founded in evidence 20,21 …”
Section: Magnesium Sulfatementioning
confidence: 99%
“…These recommendations reiterated that ACS should be used up to 34 weeks of gestation (Box 1). In making its recommendations, the GDG drew on the 2020 Cochrane review, 23 and also on evidence from a mixed‐methods systematic review on factors affecting the implementation of ACS 34 . The latter review highlighted that ensuring appropriate ACS use needs accurate gestational age assessment, consistent guidelines and training for providers, as well as sufficient supplies and trained, well‐supported staff.…”
Section: Who 2022 Recommendations On Acs To Improve Preterm Birth Out...mentioning
confidence: 99%